Bank volatility connectedness in South East Asia - Kamil Yılmaz (Koç University-TÜSİAD Economic Research Forum (ERF), 2018)
This paper presents an analysis of the volatility connectedness of major bank stocks in the South East Asia (SEACEN) region between 2004 and 2016. Applying the Diebold-Yilmaz Connectedness Index (DYCI) framework to daily stock return volatilities of major banks in the region, we obtain results that help us uncover valuable information on the region's static and dynamic bank volatility network. The volatility connectedness increased substantially during the US financial crisis (from 2007 to 2009) and during the European sovereign debt and banking crisis in 2011. The recent increase in the total connectedness has resulted from temporary financial shocks on a global scale. Once included in the analysis, the global systemically important banks (GSIBs) from the U.S. and Europe generate substantial volatility connectedness to SEACEN banks. We also identify country clusters in the banking volatility network. Major Indian, Taiwanese and Chinese banks generate volatility connectedness to their counterparts in other countries of the region. Finally, we show that the region's bank volatility network becomes tighter during systemic events; banks from different countries in the region generate volatility connectedness to the others.
Keywords: C32; G21; 330; Systemic risk; Connectedness; Network; Global Systemically Important Banks; Vector Autoregression; Variance decomposition; South East Asia